Dysregulated Plasma Membrane Turnover Underlying Dendritic Pathology in Neurodegenerative Diseases - Chung, Chang Geon; Park, Sung Soon; Park, Jeong Hyang; Lee, Sung Bae (Frontiers in Cellular Neuroscience, 2020)
Due to their enormous surface area compared to other cell types, neurons face unique challenges in properly handling supply and retrieval of the plasma membrane (PM)—a process termed PM turnover—in their distal areas. Because of the length and extensiveness of dendritic branches in neurons, transport of materials needed for PM turnover from soma to distal dendrites will be inefficient and quite burdensome for somatic organelles. To meet local demands, PM turnover in dendrites most likely requires local cellular machineries, such as dendritic endocytic and secretory systems, dysregulation of which may result in dendritic pathology observed in various neurodegenerative diseases (NDs). Supporting this notion, a growing body of literature provides evidence to suggest the pathogenic contribution of dysregulated PM turnover to dendritic pathology in certain NDs. In this article, we present our perspective view that impaired dendritic endocytic and secretory systems may contribute to dendritic pathology by encumbering PM turnover in NDs.